The Proportion of Complementary and Alternative Medicine Utilization Among Saudi Population for Eye Care: Cross-Sectional Study - AlSalman, Salma (Cureus, 2021)
Purpose To estimate the prevalence, determinants and perceived benefit of complementary and alternative medicine (CAM) use for ophthalmic purposes among the Saudi population. Methods A cross-sectional study was carried out in 2019 targeting visitors of King Khaled Eye Specialist Hospital (KKESH), Riyadh, Saudi Arabia. The survey had 18 questions in Arabic regarding the use of CAM for eye ailments. The magnitude was associated to the demographic and eye-related factors. Results We interviewed 999 participants. The prevalence of CAM usage was 21.9% (95% confidence interval 19.3; 24.5). Castor oil (49.3%), antimony (khohl alethmed) (40.6%), chamomile (19.6%), and green tea leaves (11.4%) were the most common medications used. Other traditional eye treatments included eye vitamins, faith healing (prayer, reciting Quran, Zamzam water), cautery, cupping, and acupuncture. Conclusions One in five Saudi eye patients used CAM. The factors governing this health behavior should be studied to change this practice pattern.